Identification of Differential Responses of Goat PBMCs to PPRV Virulence Using a Multi-Omics Approach - Eloiflin, Roger-Junior; Auray, Gaël; Python, Sylvie; Rodrigues, Valérie; Seveno, Martial; Urbach, Serge; El Koulali, Khadija; Holzmuller, Philippe; Totte, Philippe; Libeau, Genevieve; Bataille, Arnaud; Summerfield, Artur (Frontiers in Immunology, 2021)
Peste des petits ruminants (PPR) is an acute transboundary infectious viral disease of small ruminants, mainly sheep and goats. Host susceptibility varies considerably depending on the PPR virus (PPRV) strain, the host species and breed. The effect of strains with different levels of virulence on the modulation of the immune system has not been thoroughly compared in an experimental setting so far. In this study, we used a multi-omics approach to investigate the host cellular factors involved in different infection phenotypes. Peripheral blood mononuclear cells (PBMCs) from Saanen goats were activated with a T-cell mitogen and infected with PPRV strains of different virulence: Morocco 2008 (high virulence), Ivory Coast 1989 (low virulence) and Nigeria 75/1 (live attenuated vaccine strain). Our results showed that the highly virulent strain replicated better than the other two in PBMCs and rapidly induced cell death and a stronger inhibition of lymphocyte proliferation. However, all the strains affected lymphocyte proliferation and induced upregulation of key antiviral genes and proteins, meaning a classical antiviral response is orchestrated regardless of the virulence of the PPRV strain. On the other hand, the highly virulent strain induced stronger inflammatory responses and activated more genes related to lymphocyte migration and recruitment, and inflammatory processes. Both transcriptomic and proteomic approaches were successful in detecting viral and antiviral effectors under all conditions. The present work identified key immunological factors related to PPRV virulence in vitro.